2020
DOI: 10.1038/s41598-020-69695-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes profiles in a combined mouse model of Parkinsonism and colitis

Abstract: Different cellular mechanisms have been described as being potentially involved in the progression of neurodegeneration in Parkinson's disease, although their role is still unclear. The present study aimed to identify in detail, through differentially expressed genes analysis by bioinformatics approaches, the molecular mechanisms triggered after a systemic insult in parkinsonian mice. To address this objective, we combined a dextran sodium sulfate (DSS)-induced ulcerative colitis experimental mice model with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…A study showed that acute DSS-induced colitis enhanced infiltration of the hippocampus with periphery immune cells, along with increased pro-inflammatory cytokines and inflammatory M1-like microglia [ 146 ]. A recent gene analysis study has provided insights into the involvement of systemic inflammation after colon injury, which is related to the degeneration process of PD [ 147 ]. Scientists combined a DSS-induced UC experimental mice model with an acute 1-methyl-4-phenyl-1,2,3,6-tetradropyridine (MPTP) intoxication.…”
Section: Intestinal Dysfunctions In Pdmentioning
confidence: 99%
“…A study showed that acute DSS-induced colitis enhanced infiltration of the hippocampus with periphery immune cells, along with increased pro-inflammatory cytokines and inflammatory M1-like microglia [ 146 ]. A recent gene analysis study has provided insights into the involvement of systemic inflammation after colon injury, which is related to the degeneration process of PD [ 147 ]. Scientists combined a DSS-induced UC experimental mice model with an acute 1-methyl-4-phenyl-1,2,3,6-tetradropyridine (MPTP) intoxication.…”
Section: Intestinal Dysfunctions In Pdmentioning
confidence: 99%
“…Tumor necrosis factor (TNF) signaling pathway was also found to be a key pathway involved in PD pathogenesis 19 . Analyses of differentially expressed gene profiles in experimental mouse model of MPTP induced PD revealed increased expression of systemic inflammation and programmed cell death genes 20 Zhang et al reported decreased expression of complex I transcripts and increased expression of heat shock proteins and some anti-apoptotic gene groups in PD patients 21 . Durrenberger et al showed upregulation of P2X7 and NOS pathways thereby emphasizing that extracellular ATP and reactive astrocytes are responsible of microglial activation and subsequent release of proinflammatory cytokines that contribute to dopaminergic cell death 22 .…”
Section: Introductionmentioning
confidence: 99%
“…In this line, Martínez et al were the first to check the effect of acute colonic inflammation induced by DSS pre-treatment on MPTP induced Parkinsonism mouse model. Their findings demonstrated that DSS-induced injury circumscribed to the colon exacerbates DAergic neurodegeneration and glial response in the nigrostriatal pathway 83 . Our immunofluorescence experiment results supported previous research and showed co-localization of α-syn in TH + neurons of SNpc in rotenone treated pre colitic mice compared to the control group.…”
Section: Discussionmentioning
confidence: 98%